The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.pai.0000168591.58721.a6
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Is Unlikely to Be Involved in Directly Regulating Angiogenesis in Human Breast Cancer

Abstract: Angiogenesis is a fundamental component of oncogenesis. Angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet derived-endothelial cell growth factor/thymidine phosphorylase (PD-ECGF/TP) are generated from tumor cells to provide tumor growth and are thought to be regulated via the HER2 oncogene, whose amplification is the most common genetic alteration in breast cancer. The present study aimed to evaluate the immunoreactivity of angiogenic factors (VEGF, PD-ECGF/TP) and microvessel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…Although HER2 signaling is believed to promote tumour angiogenesis (Kumar and Yarmand-Bagheri, 2001), we found no association between HER2 overexpression and MVD, in keeping with previous results (Vogl et al, 2006). In contrast, others observed an association of MVD and HER2 overexpression in small series of patients with node-negative disease (Koukourakis et al, 2003).…”
Section: Discussionsupporting
confidence: 68%
“…Although HER2 signaling is believed to promote tumour angiogenesis (Kumar and Yarmand-Bagheri, 2001), we found no association between HER2 overexpression and MVD, in keeping with previous results (Vogl et al, 2006). In contrast, others observed an association of MVD and HER2 overexpression in small series of patients with node-negative disease (Koukourakis et al, 2003).…”
Section: Discussionsupporting
confidence: 68%
“…In the literature, some studies have reported that there is no relationship between mVD and prognostic parameters such as patient's age (25,27), histological grade (28), lymphovascular invasion (9), estrogen and progesterone receptor status (27), HEr2/neu overexpression (27). On the other hand, there are also some other studies that found a significant relationship between high mVD and patient's age (29), high histologic grade (16,25,27), presence of lymphovascular invasion (30), estrogen (16,22) and progesterone receptor negativity (22) and HEr2/neu overexpression (31).…”
Section: Discussionmentioning
confidence: 99%
“…One of the reason of this may be using different antibodies such as CD34, CD31, Factor VIII and CD105 to highlight the microvessels (24,32,33). In the literature, some studies reported that the anti-CD34 monoclonal antibody is more sensitive than the anti-CD31 antibody and anti-factor VIII-related antigens in the calculation of mVD in breast cancer (31,32). Therefore, we used the anti-CD34 monoclonal antibody to calculate the mVD.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular target of interest in this respect is vascular endothelial growth factor (VEGF)-A. VEGF-A is involved in the development and maintenance of tumor angiogenesis and is involved early during tumorigenesis. Various studies have reported overexpression of VEGF-A in the breast cancer microenvironment, compared with normal breast tissue (2)(3)(4)(5). All VEGF-A splice variants are bound by the clinically used monoclonal antibody bevacizumab.…”
mentioning
confidence: 99%